Volunteering for Health Services in the Middle Part of Ghana: In Whose Interest? - Afari-Asiedu, S.; Asante, K.P.; Senah, K.; Abdulai, M.A.; Afranie, S.; Mahama, E.; Anane, E.A.; Abukari, M.; Darko, M.L.; Febir, L.G.; Owusu-Agyei, S. (International Journal of Health Policy and Management, 2018)
Background In many developing countries like Ghana, community volunteers assist in the provision of certain health services to rural and hard-to-reach communities. This study examined factors that influence the motivation and retention of community-based volunteers supporting with work on health-related activities at the community level in Ghana. Methods Using a sequential mixed-method design, a cross-sectional survey was carried out among 205 selected community-based volunteers in Kintampo North Municipality (KNM) and Kintampo South District (KSD) of Ghana between December, 2014 and February, 2015. Qualitative interviews, including 12 in-depth interviews (IDIs) among health workers and community opinion leaders and 2 focus group discussion (FGD) sessions with volunteers were conducted. Results Personal interest (32.7%) and community leaders’ selection of volunteers (30.2%) were key initial reasons for volunteering. Monetary incentives such as allowance for extra duty (88.8%) and per diem (49.3%) and non-monetary incentives such as T-shirts/bags (45.4 %), food during training (52.7%), community recognition, social prestige and preferential treatment at health facilities were the facilitators of volunteers’ retention. There was a weak evidence (P = .051) to suggest that per diem for their travels is a reason for volunteers’ satisfaction. Conclusion Community-based volunteers’ motivation and retention were influenced by their personal interest in the form of recognition by community members and health workers, community leaders’ selection and other nonmonetary incentives. Volunteers were motivated by extra-duty allowance but not per diems paid for accommodation and feeding when they travel. Organizations that engage community volunteers are encouraged to strengthen the selection of volunteers in collaboration with community leaders, and to provide both non-monetary and monetary incentives to motivate volunteers.
Keywords: Community Volunteers’ Motivation; Community Volunteers’ Retention; Community Volunteers’ Satisfaction; Monetary Incentives; Non-monetary Incentives